Optimizing the Role of Mosques in Empowering the Muslim Economy in the Metaverse Era: A Case Study in Makassar City - Marhaeni Saleh,; Farid Fajrin, (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2025)
This research explores the economic potential of mosques in Makassar, focusing on their role in community empowerment through business development, social welfare, education, and digital integration. Mosques, as central hubs within their communities, provide opportunities for entrepreneurial ventures such as halal food businesses, souvenir shops, and religious education centers. These businesses cater to the needs of worshippers and the surrounding community, offering products and services that align with Islamic values. In addition to economic activities, mosques play a pivotal role in social welfare by organizing charitable events, health services, and educational programs that support the well-being of the community. The study also highlights the increasing potential of digital technologies, such as the metaverse, to enhance mosque-based economic empowerment. By utilizing virtual platforms, mosques can expand their outreach, offering online training, promoting sharia-compliant e-commerce, and facilitating discussions on economic management, reaching a broader audience beyond physical limitations. The research further emphasizes the importance of effective management, training, and mentorship for mosque administrators to ensure the sustainability of these programs. Ultimately, this research demonstrates how mosques in Makassar can leverage their economic, social, and educational functions to empower their communities, creating sustainable development opportunities that align with Islamic values. The findings provide practical insights for utilizing digital platforms in mosque activities, with the potential to replicate these models in other regions, contributing to broader social and economic progress.